THE CONCEPT OF POETRY IN THE CREATION OF ERKIN VAHIDOV, POET ISSUES OF REPRESENTATION AND INTERPRETATION OF THE FIGURE (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article describes the attitude of Erkin Vahidov to the science of poetry and poetry. In the article, opinions on the art of writing poetry and the qualities of poetry are deeply analyzed, the poet's own literary and theoretical views and opinions as a literary critic are revealed with the help of examples.